Investigation of New Energy Absorbing Mechanisms Used to Fix Rock Bolt Plates - Komurlu, Eren (Periodica Polytechnica Civil Engineering, 2023)
In this study, different plate fixing designs were tested in order to improve rock bolting performances. Instead of commonly used steel nuts, different plate fixing designs were investigated by both laboratory and site studies. In addition, the usability of nuts and energy absorbers made of the polyamide type engineering polymer was investigated to assess whether they are advantageous for the aim of supplying high-energy absorbing features. In this experimental study, deformation-controlled load tests were carried out to evaluate the bearing and energy absorption capacities of totally eight different groups of specimens. According to the findings from this study, use of the polyamide material with steel nuts as an energy absorber material, rather than using instead of steel nuts supplies good results. As another outcome, it has been determined that use of proper washers between steel nuts and polyamide absorbers can significantly improve the energy absorption performances. It has been evaluated that the energy absorption capacity of the bolt plates can be economically increased up to 10 times by using suitable polyamide energy absorbers placed between the plate and steel nut parts. It was concluded that the polyamides can be used to remarkably improve the rock bolting performances especially in the rock masses where the high energy absorption capacity property is needed, like those with rock bursting, squeezing and swelling problems.